Price, availability and affordability of medicines - Brenda S. Mhlanga; Fatima Suleman (AOSIS, 2014)
Background: Medicines play an important role in healthcare, but prices can be a barrier to patient care. Few studies have looked at the prices of essential medicines in low- and middle-income countries in terms of patient affordability. Aim: To determine the prices, availability and affordability of medicines along the supply chain in Swaziland. Setting: Private- and public-sector facilities in Manzini, Swaziland. Methods: The standardised methodology designed by the World Health Organization and Health Action International was used to survey 16 chronic disease medicines. Data were collected in one administrative area in 10 private retail pharmacies and 10 public health facilities. Originator brand (OB) and lowest-priced generic equivalent (LPG) medicines were monitored and these prices were then compared with international reference prices (IRPs). Affordability was calculated in terms of the daily wage of the lowest-paid unskilled government worker. Results: Mean availability was 68% in the public sector. Private sector OB medicines were priced 32.4 times higher than IRPs, whilst LPGs were 7.32 times higher. OBs cost473% more than LPGs. The total cumulative mark-ups for individual medicines range from 190.99% - 440.27%. The largest contributor to add-on cost was the retail mark-up (31% - 53%). Standard treatment with originator brands cost more than a day's wage. Conclusion: Various policy measures such as introducing price capping at all levels of the medicine supply chain, may increase the availability, whilst at the same time reducing the prices of essential medicines for the low income population.